2021
DOI: 10.1109/access.2021.3064202
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Data Access Approach With Queue and Stack in Optimized Hybrid Join

Abstract: As rapid decision making in business organizations gain in popularity, the complexity and adaptability of extract, transform, and load (ETL) process of near real-time data warehousing has dramatically increased. The most important part of near real-time data warehouse is to feed new data from different data sources on near-real-time basis. However, this new data is not in the format of the data warehouse therefore, it needs to be transformed into the required format by using transformation algorithms which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…However, data dispersion and heterogeneity make interrogation necessary but difficult, especially if the data is non-indexed. User studies have shown that high user latency drives customers away [8]. Similarly, queries or calls to stored procedures/user-defined functions are typically called numerous times in a relational model, either within a loop in an application program or from the WHERE/SELECT clause of the outer query [9].…”
Section: A Significance Of Usage Of Repetitive Non-indexed Queriesmentioning
confidence: 99%
“…However, data dispersion and heterogeneity make interrogation necessary but difficult, especially if the data is non-indexed. User studies have shown that high user latency drives customers away [8]. Similarly, queries or calls to stored procedures/user-defined functions are typically called numerous times in a relational model, either within a loop in an application program or from the WHERE/SELECT clause of the outer query [9].…”
Section: A Significance Of Usage Of Repetitive Non-indexed Queriesmentioning
confidence: 99%
“…In [16], the authors proposed two new optimized algorithms namely Parallel-Hybrid Join (P-HYBRIDJOIN) and Hybrid Join with Queue and Stack (QaS-HYBRIDJOIN). Both of these algorithms were extensions of the existing HYBRIDJOIN algorithm.…”
Section: Semi-stream Join Algorithmsmentioning
confidence: 99%